Pemberian Suplemen Multivitamin Kepada Anak-Anak Di SDN 2 Padang Panjang Barat, Kota Padang Panjang, Sebagai Upaya Pencegahan Stunting - Yahdian Rasyadi; Eka Desnita; Elisa Ayudia; Mutia Fatimah Azzahra; Mutia Defitri Khairunnisa; Dike Novella (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Lack of nutrition can cause stunting and cognitive development of children and reduce children's productivity at school. In the process of growth and development, nutrients and vitamins are needed. Adequacy of nutrients and vitamins can be met by consuming a variety of foods. If nutrition and vitamins are not met, it can be met by taking multivitamin supplements. In this community service, multivitamin supplements were given to children at SDN 2 West Padang Panjang, Padang Panjang City in July 2022 as an effort to reduce/prevent stunting in the city of Padang Panjang. This activity was attended by students of SDN 2 Padang Panjang Barat Grade 5 and Grade 6. The service team provided multivitamin supplements and provided education about the benefits of vitamins contained and how to consume vitamins to participants. After that the service team conducted a question and answer session to students in the class about the benefits of each vitamin. From the results of the activities, all 5th and 6th grade elementary school students have received multivitamin supplements and received education from the service team. From the question and answer with students about the benefits of vitamins contained, elementary students have been compact in answering correctly the benefits of vitamins being asked. This service activity that has been carried out has achieved its goal of preventing stunting in the city of Padang Panjang.